The Three-dimensional Images and Intracellular Calcium Analysis of Weigela Floridacv and Lonicera Japonica Thunb Pollen - Dongwu Liu; Zhiwei Chen; Xue Wang; Hongzhi Xu; Lina Wang (Nano Biomedicine and Engineering, 2009)
Confocal microscope, which is a major advance upon normal light microscope, has been used in a number of scientific fields. Moreover, the three-dimensional images of specimens can be reconstructed with confocal microscope. It is ideal to analyze the three dimensional specimens for the non-destructive, non-invasive nature of the confocal microscope. In the present studies, a series of Weigela floridacv and Lonicera japonica thunb pollen optical sections were acquired with confocal microscope. Then the three-dimensional images of the pollen were reconstructed with the software of confocal microscope. In addition, intracellular calcium in the pollens was detected with the probe Fluo-3 AM, and the distribution of calcium in the pollens was analyzed with confocal microscope. Our results indicate that it is a very easy job to analyze the three-dimensional digital images of the pollen and intracellular calcium in the pollens with confocal microscope and the probes Acridine orange (AO) and Fluo-3 AM.